2015
DOI: 10.1016/j.biomaterials.2015.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Phytomolecule icaritin incorporated PLGA/TCP scaffold for steroid-associated osteonecrosis: Proof-of-concept for prevention of hip joint collapse in bipedal emus and mechanistic study in quadrupedal rabbits

Abstract: Steroid-associated osteonecrosis (SAON) may lead to joint collapse and subsequent joint replacement. Poly lactic-co-glycolic acid/tricalcium phosphate (P/T) scaffold providing sustained release of icaritin (a metabolite of Epimedium-derived flavonoids) was investigated as a bone defect filler after surgical core-decompression (CD) to prevent femoral head collapse in a bipedal SAON animal model using emu (a large flightless bird). The underlying mechanism on SAON was evaluated using a well-established quadruped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 68 publications
(82 reference statements)
1
71
0
Order By: Relevance
“…Apart from the drug reservoir of TiO 2 nanotubes layer, a local controlled and sustained drug delivery system is also needed to avoid drug toxicity caused by burst release and extend the duration of the drug's action [32]. Among the various coating materials, PLGA is well accepted for its good degradability and strong drug-loading capacity compared with chitosan when used as a scaffold material [33,34]. The previous study showed that TiO 2 nanotubes coated with a PLGA polymer layer have extended release duration and higher level of burst release than TiO 2 nanotubes coated with chitosan [35].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the drug reservoir of TiO 2 nanotubes layer, a local controlled and sustained drug delivery system is also needed to avoid drug toxicity caused by burst release and extend the duration of the drug's action [32]. Among the various coating materials, PLGA is well accepted for its good degradability and strong drug-loading capacity compared with chitosan when used as a scaffold material [33,34]. The previous study showed that TiO 2 nanotubes coated with a PLGA polymer layer have extended release duration and higher level of burst release than TiO 2 nanotubes coated with chitosan [35].…”
Section: Discussionmentioning
confidence: 99%
“…Although histological analysis was not performed to assess the graft structure, this work developed the framework for future in vivo studies to assess the potential use of this novel ring to repair ruptured ACLs. Among the large animal models, the bipedal emu with steroid‐induced osteonecrosis has been recognized as a unique model for replicating the collapsed femoral head in patients 93. This model proposes a novel tool to develop Mg‐based hollow screws with holes allowing the injection of bone cement to promote new bone formation in the necrotic regions (Figure 7C).…”
Section: Animal Models For Studying Mg‐based Orthopedic Implantsmentioning
confidence: 99%
“…Icaritin is a hydrolytic product of icariin isolated from the traditional Chinese herbal medicine genus Epimedium . Previous studies showed that icaritin possesses a wide range of pharmacological properties, including neuron and cardiac protection , attenuation of lipopolysaccharide‐induced inflammation, and osteogenesis and bone defect repair promotion . Based on its potent therapy effects for human malignancies, icaritin has been entered into clinical trials for the treatment of PD‐L1 positive advanced hepatocellular carcinoma (phase III, ClinicalTrials.gov Identifier: NCT03236649), hepatocellular carcinoma (phase III, ClinicalTrials.gov Identifier: NCT03236636), advanced solid tumors (phase Ib, completed, ClinicalTrials.gov Identifier: NCT02496949), and advanced breast cancer (phase I, ClinicalTrials.gov Identifier: NCT01278810).…”
Section: Introductionmentioning
confidence: 99%